THE DEVELOPMENT OF SCIENCE COMIC ON LIGHT TOPIC FOR JUNIOR HIGH SCHOOL - Inziati, Ifa Ambarita (2014)
Joyful and interesting science learning now becomes the need of students nowadays. To support it, the development of creative learning media is necessary. This research is aimed to develop science comic especially in light topic for junior high school by considering four main aspects: Content, Artwork, Language, and Uniqueness, and to get the score in each aspect evaluated by experts and junior high school students. The method used in this research is descriptive quantitative with survey method. Subject of the research are from content experts, artwork expert, language expert, and students from International private school and National public school. According to research result, it can be concluded that the development of science comic is content analysis, material-source analysis, aspects analysis, and comic making which is divided into outline & storyboard and creative process, and after the development there is evaluation from experts and students as to revise it; the content and language in this science comic is very good while the artwork is good, and the overall comic is considered very good by students; and the comic rating for content aspect is 3.25, artwork aspect is 2.64, and language aspect is 3.29, and based on students, the overall rating for all aspect including uniqueness is 3.2. Suggestions from the experts and students are used to revise this science comic until it meets expert's criteria. Keyword: science comic, artwork, content, language, uniqueness Pembelajaran yang menyenangkan merupakan sebuah kebutuhan untuk pelajar masa kini. Untuk mendukung itu, pengembangan media kreatif perlu diperhatikan. Penelitian ini bertujuan untuk mengembangkan komik sains terutama di topic Cahaya untuk siswa sekolah menengah pertama dengan memperhatikan empat aspek: Content, Artwork, Language, dan Uniqueness, dan untuk mendapatkan penilaian dari masing-masing ahli dan siswa. Metode penelitian yang digunakan adalah metode deskriptif dengan survei. Partisipan dari penelitian ini adalah ahli di bidang content, artwork, language, dan siswa dari sekolah berbasis Internasional dan sekolah negeri. Hasil penelitian menunjukkan bahwa pengembangan komik sains terdiri dari analisis konten, analisis sumber bahan, analisis aspek, dan pembuatan komik yang dibagi menjadi outline dan storyboard serta proses kreatif, dan setelahnya dievaluasi oleh ahli dan siswa; Content dan Language dari komik sains itu dinilai sangat bagus sementara Artwork bernilai bagus, dan secara keseluruhan dinilai sangat bagus oleh siswa; dan rating dari aspek Content adalah 3.25, Artwork 2.64, dan Language 3.29, serta menurut siswa, secara keseluruhan rating komik sains ini termasuk Uniqueness bernilai 3.2. Saran dari ahli dan siswa digunakan sebagai bahan revisi agar komik sains ini menjadi lebih baik dan sesuai kriteria. Kata kunci: komik sains, artwork, content, language, uniqueness